EVALUASI PELAKSANAAN PEMILIHAN WALIKOTA DAN WAKIL WALIKOTA SEMARANG TAHUN 2015 - Eunike Sinthike Pelleng Eunike Sinthike Pelleng (Program Magister Ilmu Politik, Universitas Diponegoro, 2016)
In a democratic system, elections are open, free, and fair. This is one of the most important elements. The election process is in part the essence of democracy, since the general election is a mechanism for selecting leaders to guarantee periodic changes of leadership. This is meant to prevent arbitrary leaders from sitting in power. Semarang City Election 2015 is the third election organized by the Commission of Semarang. Elections are national, fair, independent, non-partisan, impartial, transparent, and professional based on the principles of the democratic election, with the participation of the entire community and not only favored individuals, so that the results can be trusted by the public. To answer these questions, this study uses qualitative research methods to conduct interviews with members of the Commission, Political Parties and LSM related parties. From the results of research and interviews, performance KPU Semarang, are in accordance with the legislation in force. Judging from the performance indicators that have been implemented, namely the quality of service, responsiveness, and accountability in the organization of the General Election of Regional Head and Deputy Head of the Semarang City, year 2015. In this interview, it can be seen by the perception of one of the LSMs, stated that the KPU’s performance is good enough. Of course there is dissatisfaction, especially in the transparency of campaign finance reports of the pair of candidates. Meanwhile, according to the applicable laws, the declaration commission must be transparent so that no such thing happens. Also in the field of personnel recruitment organization of the elections, PPK, and PPS must be rigorous with this mechanism to ensure transparency, In accordance with Act No. 22, 2007. From community assessments, the performance results of Semarang must be excellent for KPU to create a level of voter participation in the democratic party. Keywords: KPU performance of Semarang, Transparency, Service Quality, Responsiveness, Accountability.